Physiological responses to exercise in survivors of preterm birth: a meta-analysis - Michael L. Beaven; James T.D. Gibbons; Christopher W. Course; Sarah J. Kotecha; Thomas Hixson; Andrew Maiorana; Melissa Zuidersma; Sailesh Kotecha; Elizabeth F. Smith; Shannon J. Simpson (European Respiratory Review, 2025)
Rationale Survivors of preterm birth (<37 weeks' gestation) have low peak oxygen uptake, a global measure of aerobic fitness and an established predictor of increased morbidity and mortality. However, little is known about other cardiopulmonary outcome measures in this population. We addressed the hypothesis that preterm birth is associated with abnormal respiratory, cardiovascular and metabolic responses to exercise, as assessed by cardiopulmonary exercise testing, via a systematic review and meta-analysis. Methods Six databases were systematically searched up to 29 November 2024 (PROSPERO: CRD42022320775). Studies reporting cardiopulmonary outcome measures obtained during a standardised exercise test were included if they had preterm-born participants and matched term-born controls. The standardised mean difference (SMD) between pooled preterm-born and term-born cohorts was calculated using random-effects models for the meta-analysis. Results Of the 12 143 records identified, 47 cohorts were included in the final meta-analysis. At peak exercise, the preterm-born cohort (n=2149) demonstrated lower oxygen uptake (SMD −0.39, 95% CI −0.52 to −0.26), work rate (SMD −0.53, 95% CI −0.70 to −0.35), minute ventilation (SMD −0.43, 95% CI −0.60 to −0.26), tidal volume (SMD −0.38, 95% CI −0.62 to −0.15), oxygen pulse (SMD −0.47, 95% CI −0.75 to −0.19), heart rate (SMD −0.18, 95% CI −0.28 to −0.07), anaerobic threshold (SMD −0.29, 95% CI −0.49 to −0.08) and gas exchange efficiency (SMD 0.22, 95% CI 0.04 to 0.41), compared to the term-born cohort (n=1650). Conclusions In addition to a reduced peak oxygen uptake, survivors of preterm birth have impairments in the respiratory, cardiovascular and metabolic domains during cardiopulmonary exercise testing. Given that reduced aerobic capacity is associated with increased morbidity and mortality, exercise interventions that target cardiorespiratory fitness should be prioritised across the lifespan in those born preterm.